Chemical and mineralogical trends during acid‐sulfate alteration of pyroclastic basalt at Cerro Negro volcano and implications for early Mars. Issue 9 (5th September 2013) - McCollom, Thomas M.; Hynek, Brian M.; Rogers, Karyn; Moskowitz, Bruce; Berquó, Thelma S.
Abstract: [1] Acid‐sulfate alteration of pyroclastic basalts in active fumaroles at Cerro Negro volcano, Nicaragua, was studied as a means to infer the mineralogical and chemical consequences of basalt alteration in analogous environments on early Mars. At this site, recently erupted basaltic cinders are undergoing alteration by SO2 ‐bearing steam. During alteration, silicate phenocrysts, including plagioclase, olivine, and augite, react much more rapidly than basaltic glass. Secondary mineralogy is dominated by a very limited number of phases that include amorphous silica, gypsum, Fe‐bearing natroalunite, and Fe‐oxides/oxyhydroxides, including hematite and magnetite. The major element chemistry of the deposits is controlled by two processes: gradual depletion of the major cations other than Si as the basalt components decompose and elements are mobilized out of the deposits, and enrichment in Ca and S from precipitation of gypsum, with Ca apparently supplied from sources below the surface. Reaction path models constrained by these observations but extrapolated to Martian conditions predict that alteration of pyroclastic deposits in similar environments on Mars should produce a secondary mineral assemblage that includes amorphous silica, Fe‐bearing natroalunite, anhydrite, kieserite, and hematite. Iron‐bearing natroalunite was found to produce a Mössbauer signal similar to that of jarosite, suggesting that this phase should be considered as an alternative to the jarosite component identified at Meridiani Planum. Spheroidal hematite formed in close association with natroalunite suggests a pathway for formation of hematite deposits on Mars. Key Points: Acid‐sulfate alteration produces a very limited suite of secondary minerals Silica, gypsum, Fe‐bearing natroalunite, and hematite are key secondary phases Similar suite of products plus kieserite predicted for basalt alteration on Mars